The landscape of photoaging: From bench to bedside in a bibliometric analysis - Sun, Pei Hong; Yan, Wei Tong; Tian, Rui Feng; Sun, Yan; Wu, Yan (Frontiers in Public Health, 2022)
Background Bibliometric software exists as platforms providing multiple algorithms to process the data to suffice diverse goals. Interpretation of the result must be based on insight into the meaning of the original data and the algorithm used. Medical Subject Headings (MeSH) terms represent macro-level meaning of topics, keywords commonly reflect the micro-level aspects. Objective This study attempts to use these different data formats to construct an explicit model to obtain the knowledge structure and hotspots and investigate the panorama knowledge of photoaging in recent 2 decades. Methods Published studies of photoaging were obtained from PubMed and Web of Science Core Collection (WoSCC) from 2000 to 2020. Basic bibliometric information was generated by WOSCC. Major MeSH terms were performed in cluster analysis and displayed as hierarchical form to induce knowledge structure, detection algorithm on keywords was presented as timeline form to obtain hotspots, and institutional clusters labeled with keywords to achieve institutional characteristics. Results There were 2727 and 2705 studies were identified in PubMed and WoSCC, respectively. The numbers of photoaging-related studies at 3-year intervals grew steadily. The studies were performed in about 80 countries/regions. The highly frequent major MeSH terms were distributed in 7 clusters, reflecting the etiology, pathophysiology, treatment, and prevention of photoaging. The hotspots changed with the time going on, and the most recent hotspots were mitogen-activated protein kinase (MAPK), nuclear factor erythroid-derived 2-like 2 (Nrf2), and antioxidant activity. The high productive institutions labelling in the top 4 clusters were Seoul National University, University of Michigan, China Medical University, and Harvard University, with corresponding keywords of UVB, retinoic acid, Nrf2 and rejuvenation. Conclusions This study built a knowledge structure of pathophysiology, treatment and prevention of photoaging, and identified recent hotspots of MAPK, Nrf2 and antioxidant activity. Combing of them give a panorama knowledge of photoaging. We provide a framework for understanding of photoaging and pave the way for future researches.